Ministerial Decree No. 873/2013& Ministerial Decree No. 2/2014 on Amending Some Provisions of the Statute of Rules Enforcing the Provisions of The Law on Import And Export and The System of Procedures of Examination and Control on Imported and Exported Commodities - Egypt (2025)
Ministry of trade and industry decree no. 2 of the year 2014 on amending some provisions of the statute of rules Enforcing the Provisions of the Law on Import and Export and The System of Procedures of Examination and Control on Imported and Exported Commodities -- Ministry of trade and industry decree no. 873 of the year 2013 amending some provisions of the statute of rules Enforcing the Provisions of the import and exported commodity examination and control وزارة التجارة والصناعة قرار رقم 2 لسنة 2014 بتعديل بعض أحكام لائحة القواعد المنفذة لأحكام قانون الاستيراد والتصدير ونظام إجراءات فحص رقابة السلع السلع المستوردة والمصدرة – وزارة التجارة والصناعة قرار رقم 873 لسنة 2013 بتعديل بعض أحكام لائحة القواعد المنفذة لأحكام قانون الاستيراد والتصدير ونظام إجراءات فحص ورقابة السلع المستوردة والمصدرة